A kind of synthetic method of TMBP
By using the supported catalyst ruthenium/silicasilite to perform the oxidative coupling and reduction reaction of TMBP, the problems of waste generation and poor chromaticity in the existing process are solved, and TMBP preparation with high yield, high purity and high chromaticity are achieved, reducing production costs and reducing environmental pollution.
Patent Information
- Application Number
- CN202411899235.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
In the existing TMBP preparation process, a large number of metal oxidants and inorganic or organic reducing agents are required, resulting in problems of waste generation and poor color.
The supported catalyst ruthenium/metylsilite was used to perform oxidative coupling and reduction reaction through an autoclave. The sheet structure and high specific surface area of the methylsilite were used to improve the reaction efficiency, and the catalytic performance was improved by the loading of ruthenium chloride.
The yield, purity and chromaticity of TMBP is improved, the frequency of catalyst replacement and reactor cleaning is reduced, production costs are reduced, and environmental pollution is avoided.
Smart Images

Figure SMS_1 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of TMBP preparation, and in particular to a method for synthesizing TMBP. Background Art
[0002] TMBP (3,3',5,5'-tetramethylbiphenol) is a very important liquid crystal material intermediate with a wide range of uses and a large demand. Liquid crystal polymer (LCP) synthesized from TMBP is a high-performance special engineering plastic that has developed rapidly in recent years. Due to its high strength, high modulus, excellent dimensional stability, insulation, radiation resistance and chemical corrosion resistance, it is widely used in electronics, automobiles, precision machinery parts, home appliances, medical equipment and other fields. It can also be used as a modified monomer for many products such as polyester, polyurethane, polycarbonate, polysulfone, epoxy resin, etc., to manufacture excellent engineering plastics and composite materials. It can also be used as an antioxidant for rubber, emulsions and plastics, as well as a stabilizer for dye intermediates or petroleum products, and has broad application prospects.
[0003] At present, the main production method of TMBP is to use DMP (2,6-dimethylphenol) as raw material, generate the intermediate product DPQ (3,3',5,5'-tetramethyldiphenylquinone) through oxidative coupling, and then use a reducing agent to reduce the intermediate product to TMBP. However, this process route requires the use of a large amount of metal oxidant in the oxidative coupling process, and a large amount of inorganic or organic reducing agent in the reduction process, resulting in the formation of a large amount of waste. Several metal catalyst systems for oxidative coupling have been studied, but due to adverse side reactions, the CO coupling of DMP forms polyphenylene ether, resulting in poor chromaticity of the obtained product and difficulty in separating the catalyst. Therefore, the selectivity of CC coupling of DMP to form diphenylquinone is challenging.
[0004] Patent CN102659525A reports a method for preparing TMBP, using DMP as a raw material, using a homemade copper amine complex as a catalyst for an oxidative coupling reaction to obtain DPQ, and then using the raw material itself as a reducing agent to perform a reduction reaction at 135-160°C to obtain TMBP. This method uses the raw material itself as a reducing agent, resulting in a low product yield, and the product obtained by this method is a yellow solid powder with poor chromaticity.
[0005] Patent CN114308028A reports a method for reducing dibenzoquinone, using Pd-C, Pt-C, Rh-C, Raney nickel, etc. as catalysts, and introducing hydrogen at the reaction temperature and pressure for reduction. However, this process requires strict control of the reaction conditions, otherwise the double bonds in the benzoquinone may be completely reduced and the target product cannot be obtained.
[0006] In addition, US Patent US2018 / 185299 reports a method for preparing 3,3',5,5'-tetraisopropylbiphenyl phenol, using 2,6-diisopropylphenol as a raw material and an inorganic salt (preferably silver carbonate and anhydrous magnesium sulfate) as an oxidant to carry out an oxidative coupling reaction to obtain 3,3',5,5'-tetraisopropylbiphenylquinone, and then using hydrosulfite as a reducing agent to carry out a reduction reaction to obtain 3,3',5,5'-tetramethylbiphenyl phenol. This method requires the use of a large amount of oxidants and reducing agents, and produces a large amount of waste liquid, which is not conducive to environmental protection.
[0007] In summary, it is extremely necessary to find a suitable catalyst to cooperate with an oxidant and a reductant to realize the oxidative coupling of DMP and the reduction of the intermediate product DPQ. After the reaction is completed, the catalyst can be easily separated and reused, thereby improving the yield and purity of TMBP and the color of the product. Summary of the invention
[0008] To solve at least one of the above problems, the present invention provides a method for synthesizing TMBP, comprising the following steps:
[0009] Step S100, dissolving ruthenium chloride in deionized water, adding magadiite under nitrogen protection and stirring, immersing and stirring at the reaction temperature, filtering, washing and drying after the stirring is completed, to obtain a supported catalyst ruthenium / magadiite;
[0010] Step S200, adding the ruthenium / magadiite, 2,6-dimethylphenol and tetrahydrofuran obtained in step S100 into a high-pressure reactor, introducing oxygen, and performing an oxidative coupling reaction at a reaction temperature and pressure, and obtaining an oxidation reaction product after the reaction is completed;
[0011] Step S300, cooling the oxidation reaction product obtained in step S200, replacing the oxygen in the kettle with nitrogen, then introducing hydrogen to replace the nitrogen in the kettle, performing a reduction reaction at the reaction temperature and pressure, and obtaining a reduction reaction product after the reaction is completed;
[0012] Step S400, filtering the reduction reaction product obtained in step S300 to obtain a filtrate and ruthenium / magadiite;
[0013] Step S500, distilling and concentrating the filtrate obtained in step S400 to obtain tetrahydrofuran and TMBP.
[0014] In the above technical scheme, magadiite has a lamellar structure, a large specific surface area, good ion exchangeability and strong adsorption. After magadiite is used as a carrier and ruthenium chloride is loaded, a supported catalyst ruthenium / magadiite having both oxidation catalytic ability and reduction catalytic ability can be obtained; ruthenium / magadiite can not only improve the conversion rate of DMP, the selectivity of DPQ and the yield of DPQ in the oxidation reaction product, but also improve the yield of TMBP, the purity of TMBP and the chromaticity of TMBP in the reduction reaction product. In the entire production process, there is no need to replace the catalyst and the reactor, and only the type of gas phase in the reactor needs to be changed to prepare high-quality TMBP; in addition, the supported catalyst ruthenium / magadiite is easy to separate and can be filtered and collected and reused, thereby reducing production costs and avoiding environmental pollution.
[0015] Preferably, the method further comprises the following steps: Step S600, reusing the ruthenium / magadiite obtained in Step S400 and the tetrahydrofuran obtained in Step S500.
[0016] Preferably, in step S100, the mass ratio of ruthenium chloride, deionized water and magadiite is (2-100):1000:(10-50); in step S200, the mass ratio of ruthenium / magadiite, 2,6-dimethylphenol and tetrahydrofuran is (2-5):10:(90-900).
[0017] Preferably, in step S100, the immersion temperature is 0-50°C, the immersion time is 0.5-24h, the drying temperature is 20-80°C, and the drying time is 1-12h; in step S200, the oxygen pressure is 0.2-3Mpa, the reaction temperature is 50-100°C, and the reaction time is 5-20h; in step S300, the hydrogen pressure is 0.2-3Mpa, the reaction temperature is 10-70°C, and the reaction time is 1-10h.
[0018] Preferably, in step S100, the preparation of magadiite comprises the following steps:
[0019] Step S110, after washing, acid washing, filtering and drying the silicon source, a pretreated silicon source is obtained, sodium carbonate and sodium hydroxide are dissolved in deionized water to obtain an alkaline solution, the pretreated silicon source is added to the alkaline solution, mixed and stirred evenly, and reacted at the reaction temperature, and after the reaction is completed, filtered, washed with water, and dried to obtain magadiite powder.
[0020] In the above technical scheme, the silicon source is first pretreated, water washing can effectively remove water-soluble impurities in the silicon source, and acid washing can improve the dispersibility of the silicon source, enhance its adsorption performance and improve the surface performance; the pretreated silicon source after water washing and acid washing can be reacted with an alkaline solution through a hydrothermal synthesis method to obtain high-quality pure phase magadiite powder.
[0021] Preferably, the silicon source is white carbon black or a mixture of white carbon black and nano-attapulgite in a mass ratio of (5-10):1; the mass ratio of sodium carbonate, sodium hydroxide, deionized water and pretreated silicon source is 5:1:(150-200):(40-50); the acid pickling uses a hydrochloric acid solution with a volume 3-5 times the volume of the silicon source, and the silicon source is ultrasonically emulsified and dispersed in the hydrochloric acid solution at 60-70°C for 60-90 minutes, and the concentration of the hydrochloric acid solution is 0.5-1wt%; the reaction temperature of the alkaline solution and the pretreated silicon source is 160-220°C, and the reaction time is 36-48h.
[0022] In the above technical scheme, the silicon source can be a mixture of white carbon black and nano-attapulgite. Nano-attapulgite is a magnesium aluminum silicate with a layered chain structure, a large number of pore structures and a large internal and external specific surface area, and has excellent ion exchange and adsorption properties. The use of nano-attapulgite and white carbon black as a silicon source can further improve the ion exchange and adsorption properties of magadiite powder.
[0023] Preferably, the preparation of magadiite further comprises the following steps:
[0024] Step S120, dissolving nickel chloride in deionized water, then adding the magadiite powder in step S110, mixing and stirring evenly, reacting at the reaction temperature, filtering, washing, and drying after the reaction to obtain nickel-intercalated magadiite powder;
[0025] Step S130, mixing and stirring the zinc salt, 2-methylimidazole and the first solvent evenly, reacting at the reaction temperature, filtering and drying after the reaction is completed to obtain zeolite powder; mixing and stirring the zeolite powder, nickel chloride and the second solvent evenly, reacting at the reaction temperature, filtering and drying after the reaction is completed to obtain nickel-loaded zeolite powder;
[0026] Step S140, mixing and stirring the nickel-intercalated magadiite powder in step S120, the nickel-loaded zeolite powder in step S130, and the activated carbon fiber to obtain a first powder;
[0027] Step S150, mixing the magadiite powder and sodium carbonate in step S110 and stirring them uniformly to obtain a second powder;
[0028] Step S160, putting the first powder in step S140 into a ball rolling machine, contacting it with the silica sol sprayed in an atomized manner, rolling it into balls, and sieving it to obtain mother balls; putting the mother balls and the second powder in step S150 into a ball rolling machine, contacting it with the silica sol sprayed in an atomized manner, coating the mother balls, rolling them into balls, and sieving them to obtain coated balls;
[0029] Step S170, shaping the coated balls in step S160, freeze-drying them in vacuum after shaping, washing them with water to remove sodium carbonate after drying, and obtaining a carrier precursor; drying and calcining the carrier precursor to obtain a core-shell structured magadiite ball;
[0030] Step S180, dissolving citric acid in a hydrochloric acid solution, adding the magadiite balls in step S170, mixing and stirring evenly, performing an acidification reaction at a reaction temperature, filtering, washing with water, and drying after the reaction is completed, to obtain modified magadiite balls.
[0031] In the above technical scheme, nickel-intercalated magadiite powder is obtained by step S120, nickel-loaded zeolite powder is obtained by step S130, and then the nickel-intercalated magadiite powder, nickel-loaded zeolite powder and activated carbon fiber are mixed to prepare a mother ball; the mother ball is mainly composed of magadiite powder and zeolite powder, which can improve the conversion rate of DMP and the selectivity of DPQ in the oxidative coupling reaction, and improve the yield and purity of TMBP in the reduction reaction; the nickel in the mother ball can synergize with ruthenium to improve the reaction efficiency and shorten the reaction time; the mother ball contains activated carbon fiber, which can make the mother ball calcined at high temperature The carrier has a large channel running through the entire mother ball, which improves the heat dissipation performance of the carrier; magadiite powder and sodium carbonate are mixed to prepare a coating layer, the mother ball is coated to obtain a coated ball, and the sodium carbonate on the coated ball is washed to remove the sodium carbonate on the coated ball, so as to obtain a carrier precursor with a large number of pores on the surface, which greatly increases the specific surface area of the carrier, increases the loading amount, and is beneficial to heat dissipation; after drying and calcining the carrier precursor, a core-shell structured magadiite ball can be obtained, the mother ball is the core, and the coating layer is the shell; the magadiite ball is acidified and modified with citric acid, which can further improve the surface performance of the carrier.
[0032] Preferably, in step S130, the zinc salt is at least one of zinc acetate, zinc chloride and zinc nitrate; and the first solvent and the second solvent are at least one of deionized water, methanol, ethanol, propanol and ethylene glycol.
[0033] Preferably, in step S120, the mass ratio of nickel chloride, deionized water and magadiyne powder is 10: (300-500): (25-35); in step S130, the mass ratio of zinc salt, 2-methylimidazole and the first solvent is 10: (25-30): (1000-1500); the mass ratio of zeolite powder, nickel chloride and the second solvent is (20-25): 40: (1000-1500); in step S140, the mass ratio of nickel-intercalated magadiyne powder, nickel-loaded zeolite powder and activated carbon fiber is (60-70): (20-25): (10-15), and the length of the activated carbon fiber is 2-3 mm and the diameter is 5-20 μm; In step S150, the mass ratio of magadiite powder and sodium carbonate is 100:(20-50); in step S160, the solid content of silica sol is 30-40wt%; the mass ratio of the first powder to silica sol is 100:(40-50); the mass ratio of the second powder to silica sol is 100:(40-50); in step S180, the mass ratio of citric acid, hydrochloric acid solution and magadiite balls is 1:(40-50):(2-5), and the concentration of the hydrochloric acid solution is 5-10wt%.
[0034] Preferably, in step S120, the reaction temperature is 60-100°C, and the reaction time is 2-10 hours; in step S130, the reaction temperature of zinc salt, 2-methylimidazole and the first solvent is 0-500°C, and the reaction time is 15-24 hours; the reaction temperature of zeolite powder, nickel chloride and the second solvent is 45-55°C, and the reaction time is 15-24 hours; in step S160, the diameter of the mother ball is 3-5 mm; the diameter of the coated ball is 5~8mm; in step S170, the coated balls are freeze-dried and pre-frozen at -10℃ for 0.5h, then cooled to -30℃ for 2h, and finally heated to room temperature and maintained for 0.5h; the carrier precursor is dried at 100~120℃, dried for 1~2h, calcined at 400~500℃, and calcined for 3~4h; in step S180, the acidification temperature is 70~90℃, and the acidification time is 10~16h.
[0035] Compared with the prior art, the present invention has the following beneficial technical effects:
[0036] 1. The supported catalyst ruthenium / magadiite can improve the conversion rate of DMP, the selectivity of DPQ and the yield of DPQ in the oxidation reaction product, and at the same time improve the yield of TMBP, the purity of TMBP and the chromaticity of TMBP in the reduction reaction product. In the entire production process, there is no need to replace the catalyst and the reactor, and only the type of gas phase in the reactor needs to be changed to prepare high-quality TMBP;
[0037] 2. The supported catalyst ruthenium / magadiite is easy to separate and can be filtered and collected before reuse, which reduces production costs and avoids environmental pollution;
[0038] 3. When preparing magadiite powder, the silicon source is first pretreated. Water washing can effectively remove water-soluble impurities in the silicon source, and acid washing can improve the dispersibility of the silicon source, enhance its adsorption performance and improve the surface performance. The pretreated silicon source after water washing and acid washing can react with an alkaline solution through a hydrothermal synthesis method to obtain high-quality pure phase magadiite powder;
[0039] 4. The use of nano-attapulgite and white carbon black as a silicon source can further improve the ion exchange and adsorption properties of magadiite powder;
[0040] 5. The modified magadiite ball as a carrier has a core-shell structure. The core body is mainly composed of nickel-intercalated magadiite powder and nickel-loaded zeolite powder and has a large number of through channels, which can improve the conversion rate of DMP and the selectivity of DPQ in the oxidative coupling reaction, improve the yield and purity of TMBP in the reduction reaction, and improve the reaction efficiency and the heat dissipation performance of the carrier; the shell is mainly composed of magadiite powder and has a large number of pores. After acid modification, the surface properties of the carrier are further improved;
[0041] In summary, the present invention adopts ruthenium / magadiite as a supported catalyst. In the entire production process, high-quality TMBP with high yield, high purity and chromaticity can be obtained without replacing the catalyst and the reactor. At the same time, ruthenium / magadiite is easy to separate and can be reused, thereby reducing production costs and avoiding environmental pollution. DETAILED DESCRIPTION
[0042] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0043] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below. Example 1
[0044] The white carbon black was first washed with deionized water for 3 times, and then the washed white carbon black was added to 3 times the volume of a hydrochloric acid solution with a concentration of 1wt%, and ultrasonically emulsified and dispersed at 65°C for 60min for acid washing. After the acid washing, it was filtered and dried to obtain a pretreated silicon source; 5 parts by mass of sodium carbonate and 1 part by mass of sodium hydroxide were dissolved in 150 parts by mass of deionized water to obtain an alkaline solution, 40 parts by mass of the pretreated silicon source were added to the alkaline solution, mixed and stirred evenly, and reacted at 180°C for 40h. After the reaction was completed, it was filtered, washed with water, and dried to obtain magadiite powder;
[0045] 20 parts by mass of ruthenium chloride were dissolved in 1000 parts by mass of deionized water, and 10 parts by mass of magadiite powder were added under nitrogen protection and stirring. After impregnation and stirring at 25°C for 12 hours, the filter cake was collected by filtration, and the filter cake was washed with deionized water for 3 times, and then placed in a vacuum drying oven at 65°C for 6 hours to obtain a supported catalyst ruthenium / magadiite;
[0046] 6.4 parts by mass of ruthenium / magadiite, 20 parts by mass of 2,6-dimethylphenol and 550 parts by mass of tetrahydrofuran were added into a high-pressure reactor, oxygen was introduced, and an oxidative coupling reaction was carried out at 70° C. and 1 MPa for 15 hours, and an oxidation reaction product was obtained after the reaction was completed;
[0047] The oxidation reaction product is cooled to room temperature, and the oxygen in the kettle is replaced by nitrogen. Subsequently, hydrogen is introduced to replace the nitrogen in the kettle, and a reduction reaction is carried out at 50°C and 1MPa for 4 hours. After the reaction, a reduction reaction product is obtained; the reduction reaction product is filtered to obtain a filtrate and ruthenium / magadiite; the filtrate is distilled and concentrated to obtain tetrahydrofuran and TMBP; the ruthenium / magadiite obtained by filtration and the tetrahydrofuran obtained by concentration are reused. Example 2
[0048] The difference between this embodiment and embodiment 1 is that during the oxidative coupling reaction, the oxidative coupling reaction time is 18 hours. Example 3
[0049] The difference between this embodiment and embodiment 1 is that when preparing ruthenium / magadiite, ruthenium chloride is 30 parts by mass. Example 4
[0050] The difference between this embodiment and embodiment 1 is that when preparing ruthenium / magadiite, ruthenium chloride is 40 parts by mass. Example 5
[0051] The difference between this embodiment and embodiment 1 is that when preparing ruthenium / magadiite, ruthenium chloride is 50 parts by mass. Example 6
[0052] The difference between this embodiment and embodiment 1 is that when preparing ruthenium / magadiite, ruthenium chloride is 50 parts by mass; during the oxidative coupling reaction, ruthenium / magadiite is 7.5 parts by mass; during the reduction reaction, the reduction reaction time is 3.5 hours. Example 7
[0053] The difference between this embodiment and embodiment 1 is that when preparing ruthenium / magadiite, ruthenium chloride is 50 parts by mass; during the oxidative coupling reaction, ruthenium / magadiite is 8.5 parts by mass; during the reduction reaction, the reduction reaction time is 3 hours. Example 8
[0054] The difference between this embodiment and embodiment 1 is that when preparing ruthenium / magadiite, ruthenium chloride is 50 parts by mass; during the oxidative coupling reaction, ruthenium / magadiite is 9.5 parts by mass; during the reduction reaction, the reduction reaction time is 2.5 hours. Example 9
[0055] The difference between this embodiment and embodiment 1 is that during the oxidative coupling reaction, the oxygen pressure is 1.5 MPa; during the reduction reaction, the hydrogen pressure is 1.5 MPa. Example 10
[0056] The difference between this embodiment and embodiment 1 is that during the oxidative coupling reaction, the oxidative coupling reaction temperature is 90°C; during the reduction reaction, the reduction reaction temperature is 70°C. Embodiment 11
[0057] The difference between this embodiment and embodiment 1 is that when preparing the magadiite powder, the silicon source is a mixture of white carbon black and nano-attapulgite in a mass ratio of 5:1. Example 12
[0058] The difference between this embodiment and embodiment 1 is that when preparing magadiite powder, the silicon source is a mixture of white carbon black and nano-attapulgite in a mass ratio of 10:1, and the pretreated silicon source is 50 parts by mass. Example 13
[0059] The difference between this embodiment and embodiment 11 is that the magadiite powder is further prepared into modified magadiite balls having a core-shell structure, and the specific steps are as follows:
[0060] Dissolve 10 parts by mass of nickel chloride in 350 parts by mass of deionized water, then add 25 parts by mass of magadiite powder, mix and stir evenly, react at 80° C. for 4 hours, filter, wash and dry after the reaction to obtain nickel-intercalated magadiite powder;
[0061] 10 parts by mass of zinc nitrate, 25 parts by mass of 2-methylimidazole and 1000 parts by mass of ethanol were mixed and stirred evenly, reacted at 25°C for 24 hours, filtered and dried after the reaction to obtain zeolite powder; 20 parts by mass of zeolite powder, 40 parts by mass of nickel chloride and 1000 parts by mass of ethanol were mixed and stirred evenly, reacted at 55°C for 20 hours, filtered and dried after the reaction to obtain nickel-loaded zeolite powder;
[0062] 60 parts by mass of nickel-intercalated magadiite powder, 25 parts by mass of nickel-loaded zeolite powder and 15 parts by mass of activated carbon fiber are mixed and stirred to obtain a first powder; 100 parts by mass of magadiite powder and 20 parts by mass of sodium carbonate are mixed and stirred to obtain a second powder; 100 parts by mass of the first powder are put into a ball rolling machine, contacted with 40 parts by mass of 35wt% silica sol sprayed in an atomizing manner, rolled into balls and sieved to obtain mother balls with a diameter of 3mm; the mother balls and 100 parts by mass of the second powder are put into a ball rolling machine, contacted with 40 parts by mass of 35wt% silica sol sprayed in an atomizing manner, rolled into balls and sieved to obtain mother balls with a diameter of 3mm; The mother ball is contacted with 40 parts by mass of 35wt% silica sol, the mother ball is coated, rolled into balls and sieved to obtain coated balls with a diameter of 5mm; the coated balls are shaped, and vacuum freeze-dried after shaping, and the freeze-drying is first pre-frozen at -10°C for 0.5h, then cooled to -30°C for 2h, and finally heated to room temperature and maintained for 0.5h. After drying, the sodium carbonate is removed by washing with water to obtain a carrier precursor; the carrier precursor is dried at 100°C for 2h, and calcined at 400°C for 4h to obtain a core-shell structured magadiite ball;
[0063] 1 part by mass of citric acid was dissolved in 50 parts by mass of 5wt% hydrochloric acid solution, and 2 parts by mass of magadiite balls were added. The mixture was stirred evenly, and then acidified at 80°C for 12h. After the reaction was completed, the mixture was filtered, washed with water, and dried to obtain modified magadiite balls. Embodiment 14
[0064] The difference between this embodiment and embodiment 13 is that when preparing the modified magadiite balls, the magadiite balls are 5 parts by mass. Embodiment 15
[0065] The difference between this embodiment and embodiment 13 is that when preparing the magadiite balls, the diameter of the mother ball is 5 mm and the diameter of the coated ball is 6 mm. Example 16
[0066] The difference between this embodiment and embodiment 13 is that when preparing the magadiite balls, the diameter of the mother ball is 3 mm and the diameter of the coated ball is 8 mm. Embodiment 17
[0067] The difference between this embodiment and embodiment 13 is that when preparing the first powder, the nickel-intercalated magadiite powder is 70 parts by mass, the nickel-loaded zeolite powder is 20 parts by mass, and the activated carbon fiber is 10 parts by mass. Embodiment 18
[0068] The difference between this embodiment and embodiment 13 is that when preparing the nickel intercalated magadiite powder, the magadiite powder is 35 parts by mass. Embodiment 19
[0069] The difference between this embodiment and embodiment 13 is that when preparing the zeolite powder, the amount of 2-methylimidazole is 30 parts by mass; when preparing the nickel-loaded zeolite powder, the amount of zeolite powder is 25 parts by mass. Embodiment 20
[0070] The difference between this embodiment and embodiment 13 is that when preparing the zeolite powder, zinc nitrate is replaced by zinc acetate, and ethanol is replaced by deionized water.
[0071] Comparative Example 1
[0072] The difference between this comparative example and Example 1 is that, when preparing the supported catalyst, the magadiite powder is replaced with cerium oxide powder to obtain ruthenium / cerium oxide.
[0073] Comparative Example 2
[0074] The difference between this comparative example and Example 1 is that, when preparing the supported catalyst, the magadiite powder is replaced with titanium dioxide powder to obtain ruthenium / titanium dioxide.
[0075] Comparative Example 3
[0076] The difference between this comparative example and Example 1 is that, when preparing the supported catalyst, the magadiite powder is replaced with alumina powder to obtain ruthenium / alumina.
[0077] Comparative Example 4
[0078] The difference between this comparative example and Example 1 is that, when preparing the supported catalyst, the magadiite powder is replaced with magnesium oxide powder to obtain ruthenium / magnesium oxide.
[0079] Comparative Example 5
[0080] The difference between this comparative example and Example 1 is that, when preparing the supported catalyst, the magadiite powder is replaced with activated carbon powder to obtain ruthenium / activated carbon.
[0081] Comparative Example 6
[0082] The difference between this comparative example and Example 1 is that, when preparing the supported catalyst, ruthenium chloride is replaced with palladium chloride to obtain palladium / magadiite.
[0083] Comparative Example 7
[0084] The difference between this comparative example and Example 1 is that, when preparing the supported catalyst, ruthenium chloride is replaced with rhodium chloride to obtain rhodium / magadiite.
[0085] Comparative Example 8
[0086] The difference between this comparative example and Example 1 is that, when preparing the supported catalyst, ruthenium chloride is replaced with platinum chloride to obtain platinum / magadiite.
[0087] Comparative Example 9
[0088] The difference between this comparative example and Example 1 is that the supported catalyst ruthenium / magadiite is replaced with ruthenium chloride.
[0089] Comparative Example 10
[0090] The difference between this comparative example and Example 1 is that the supported catalyst ruthenium / magadiite is replaced with magadiite powder.
[0091] Results
[0092] The DMP conversion rate, DPQ selectivity and DPQ yield in the oxidation reaction product of Examples 1-20 and Comparative Examples 1-10, the TMBP yield, TMBP purity, TMBP chromaticity and the number of times the catalyst can be reused in the reduction reaction product were tested. The test results are shown in Table 1.
[0093]
[0094] In combination with Table 1, in Examples 1-20, under the catalysis of ruthenium / magadiite, DMP and oxygen undergo an oxidative coupling reaction, and the oxidative coupling reaction process is as follows:
[0095]
[0096] The obtained oxidation reaction product was detected. Among the oxidation reaction products, the conversion rate of DMP was greater than 98wt%, the yield of DPQ was greater than 98wt%, the yield of TMBP was 0, and the yield of PPE was less than 1%. It can be seen that using ruthenium / magadiite as a supported catalyst can greatly improve the conversion rate of DMP and the selectivity of DPQ; under the catalysis of ruthenium / magadiite, DPQ and hydrogen undergo a reduction reaction, and the reduction reaction process is as follows:
[0097]
[0098] The obtained reduction reaction product was detected. Among the reduction reaction products, the yield of TMBP was greater than 95wt%, the purity was greater than 98wt%, and the color was white. It can be seen that using ruthenium / magadiite as a supported catalyst can greatly improve the yield, purity and color of TMBP.
[0099] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A method for synthesizing TMBP, characterized in that: The following steps are involved: Step S100, dissolving ruthenium chloride in deionized water, adding magadiite under nitrogen protection and stirring, impregnating and stirring at the reaction temperature, filtering, washing and drying after the stirring, to obtain a supported catalyst ruthenium / magadiite; the mass ratio of ruthenium chloride, deionized water and magadiite is (2-100):1000:(10-50); the preparation of the magadiite comprises the following steps: Step S110, after washing, acid washing, filtering and drying the silicon source, a pretreated silicon source is obtained, sodium carbonate and sodium hydroxide are dissolved in deionized water to obtain an alkaline solution, the pretreated silicon source is added to the alkaline solution, mixed and stirred evenly, and reacted at the reaction temperature. After the reaction is completed, the mixture is filtered, washed with water, and dried to obtain magadiite powder; the silicon source is a mixture of white carbon black and nano-attapulgite in a mass ratio of (5-10):1; the mass ratio of sodium carbonate, sodium hydroxide, deionized water and the pretreated silicon source is 5:1:(150-200):(40-50); the acid washing uses a hydrochloric acid solution with a volume 3-5 times the volume of the silicon source, and the silicon source is ultrasonically emulsified and dispersed in the hydrochloric acid solution at 60-70°C for 60-90 minutes, and the concentration of the hydrochloric acid solution is 0.5-1wt%; the reaction temperature of the alkaline solution and the pretreated silicon source is 160-220°C, and the reaction time is 36-48h; Step S200, adding the ruthenium / magadiite, 2,6-dimethylphenol and tetrahydrofuran obtained in step S100 into a high-pressure reactor, introducing oxygen, and performing an oxidative coupling reaction at a reaction temperature and pressure, and obtaining an oxidation reaction product after the reaction is completed; the mass ratio of ruthenium / magadiite, 2,6-dimethylphenol and tetrahydrofuran is (2-5):10:(90-900); Step S300, cooling the oxidation reaction product obtained in step S200, replacing the oxygen in the kettle with nitrogen, then introducing hydrogen to replace the nitrogen in the kettle, performing a reduction reaction at the reaction temperature and pressure, and obtaining a reduction reaction product after the reaction is completed; Step S400, filtering the reduction reaction product obtained in step S300 to obtain a filtrate and ruthenium / magadiite; Step S500, distilling and concentrating the filtrate obtained in step S400 to obtain tetrahydrofuran and TMBP.
2. The method for synthesizing TMBP according to claim 1, characterized in that: The following steps are also included: Step S600, reusing the ruthenium / magadiite obtained in step S400 and the tetrahydrofuran obtained in step S500.
3. The method for synthesizing TMBP according to claim 1, characterized in that: In step S100, the immersion temperature is 0-50°C, the immersion time is 0.5-24h, the drying temperature is 20-80°C, and the drying time is 1-12h; in step S200, the oxygen pressure is 0.2-3Mpa, the reaction temperature is 50-100°C, and the reaction time is 5-20h; in step S300, the hydrogen pressure is 0.2-3Mpa, the reaction temperature is 10-70°C, and the reaction time is 1-10h.
Citation Information
Patent Citations
Preparation method of 3,3'5,5'-tetraalkyl-4,4'-biphenyl diphenol
CN102659525A
The use of diphenol in preparation of medicines for prevention and treatment of cerebral ischemia
US20180185299A1
TMBP catalytically synthesized by one-pot method
CN110479378A
Preparation of crystalline zeolites using magadiite
US4676958A